Effectiveness of prone position with its moderating factors in non-intubated acute respiratory distress syndrome patients: a meta-analysis - Tan, Julianus Yudhistira; Togatorop, Via Eliadora; Koerniawan, Dheni; Kosasih, Cecep Eli; Mediani, Henny Suzana (Jurnal Ners, 2024)
Introduction: While numerous meta-analyses have explored the efficacy of awake prone position (APP), most have concentrated solely on intubation rate among Covid-19 patients without comprehensively identifying the influencing factors. This study aims to evaluate the efficacy of APP along with its moderating factors on oxygenation, intubation rate, and mortality in non-intubated acute respiratory distress syndrome (ARDS) patients. Methods: We conducted a systematic search in PubMed, Web of Science, and CINAHL from inception to December 2022. JBI critical appraisal tools were used to assess the study quality. Random-effects model was employed to calculate pooled standardized mean difference for continuous outcomes and risk ratio for dichotomous outcomes. Results: Among the 39 studies included, most patients were suffering from Covid-19, using conventional oxygen therapy, and receiving APP outside the ICU. APP significantly improved the PaO2/FiO2 ratio (SMD=0.70, 95% CI=0.51-0.88) and SpO2/FiO2 ratio (SMD=0.76, 95% CI=0.51-1.01), while also reducing the risk of intubation (RR=0.66, 95% CI=0.51-0.85) and mortality (RR=0.62, 95% CI=0.49-0.78). Factors including severity, respiratory device, body mass index, detail of position, use of medication assistance, total duration, follow-up time, position at follow-up, and study design significantly influence the effectiveness of APP. APP did not lead to significant improvements in length of stay and adverse events Conclusions: APP is a safe and beneficial intervention, enhancing oxygenation and reducing intubation and mortality rates in non-intubated ARDS patients. Importantly, various patient and intervention characteristics should be taken into account when implementing APP. Further well-designed experimental studies are needed to strengthen the evidence base.